2011
DOI: 10.1152/jn.00991.2010
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic modulation by galanin of excitatory synaptic transmission in substantia gelatinosa neurons of adult rat spinal cord slices

Abstract: Yue HY, Fujita T, Kumamoto E. Biphasic modulation by galanin of excitatory synaptic transmission in substantia gelatinosa neurons of adult rat spinal cord slices. J Neurophysiol 105: 2337-2349, 2011. First published March 16, 2011 doi:10.1152/jn.00991.2010.-Although intrathecally administrated galanin modulates nociceptive transmission in a biphasic manner, this has not been fully examined previously. In the present study, the action of galanin on synaptic transmission in the substantia gelatinosa (SG) neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…This effect appears to be mediated by GAL 2 , presumably located on terminals of primary afferents and DH neurons, because it is mimicked by low-dose galanin (2-11), but not the GAL 1 preferential agonist M617 (Yue et al, 2011). Conversely, it was demonstrated that galanin (2-11) decreases spontaneous EPSC frequency (Alier et al, 2008).…”
Section: Painmentioning
confidence: 95%
See 3 more Smart Citations
“…This effect appears to be mediated by GAL 2 , presumably located on terminals of primary afferents and DH neurons, because it is mimicked by low-dose galanin (2-11), but not the GAL 1 preferential agonist M617 (Yue et al, 2011). Conversely, it was demonstrated that galanin (2-11) decreases spontaneous EPSC frequency (Alier et al, 2008).…”
Section: Painmentioning
confidence: 95%
“…Ablation of primary afferent innervation into the spinal cord does not appear to significantly decrease galanin binding (indicative of galanin receptor expression/levels) in the spinal cord, suggesting galanin receptors are present mainly on postsynaptic neurons (Kar and Quirion, 1994;Zhang et al, 1998). However, more recent studies imply that galanin also functions presynaptically in the DH, likely via GAL 2 (Alier et al, 2008;Yue et al, 2011). It is noteworthy that galanin and galanin receptor binding have also been detected in monkey DRG and spinal cord (Zhang et al, 1993a(Zhang et al, , 1995a, and galanin is expressed in human DRG (Landry et al, 2003).…”
Section: Painmentioning
confidence: 98%
See 2 more Smart Citations
“…Galanin produced a biphasic dose-dependent effect on spinal nociceptive excitability. In pain processing, the activation of postsynaptic GAL1 extent anti-nociceptive actions with decrease membrane excitability of dorsal horn neurons at high doses, while the activation of presynaptic GAL2 media pro-nociceptive action at low doses (28,29). Spinal parvalbumin(PV) positive cells mainly distribute in lamina I-III.…”
Section: Gabaergic Neuronal Circuit In Spinal Dorsal Hornmentioning
confidence: 99%